Making the most of Sibelius in the Classroom. (1st February 2019) - Young, Will
Abstract : AVID's flagship notation software includes a number of features that many users are unaware of and some of these can be invaluable tools in a classroom setting. Will Young looks at how some of them can be used to effectively communicate feedback to students and streamline your workflow